Oestrogen receptors β1 and βcx have divergent roles in breast cancer survival and lymph node metastasis - Rosin, G; de Boniface, J; Karthik, G M; Frisell, J; Bergh, J; Hartman, J (British journal of cancer, 2014)
Background: The expression of oestrogen receptor (ER) α characterises a subset of breast cancers associated with good response to endocrine therapy. However, the clinical significance of the second ER, ER β 1, and its splice variant ER β cx is still unclear. Methods: We here report an assessment of ER α , ER β 1 and ER β cx by immunohistochemistry using quantitative digital image analysis of 340 primary tumours and corresponding sentinel lymph nodes. Results: No differences were seen in ER levels in primary tumours vs lymph node metastases. ER β 1 and ER β cx were equally distributed among age groups and tumour histological grades. Loss of ER β 1 in the primary tumour was strongly associated with poor survival. Its prognostic impact was particularly evident in young patients and in high-grade tumours. The worst outcome was seen in the tumours lacking both ER α and ER β 1. ER β cx expression in the primary tumour correlated with a higher risk of lymph node metastasis, and with poor survival when expressed in sentinel node lymphocytes. Conclusions: Our study reveals highly significant although antagonising roles of ER β 1 and ER β cx in breast cancer. Consequently, we suggest that the histopathological assessment of ER β 1 is of value as a prognostic and potentially predictive biomarker.